Why sketching may aid learning from science texts: contrasting sketching with written explanations - Scheiter, Katharina; Schleinschok, Katrin; Ainsworth, Shaaron E. (Wiley, 2017)
The goal of this study was to explore two accounts for why sketching during learning from text is helpful: (1) sketching acts like other constructive strategies such as self-explanation because it helps learners to identify relevant information and generate inferences; or (2) that in addition to these general effects, sketching has more specific benefits due to the pictorial representation that is constructed. Seventy-three seventh-graders (32 girls, M = 12.82 years) were first taught how to either create sketches or self-explain while studying science texts. During a subsequent learning phase, all students were asked to read an expository text about the greenhouse effect. Finally, they were asked to write down everything they remembered and then answer transfer questions. Strategy quality during learning was assessed as the number of key concepts that had either been sketched or mentioned in the self-explanations. The results showed that at an overall performance level there were only marginal group differences. However, a more in-depth analysis revealed that whereas no group differences emerged for students implementing either strategy poorly, the sketching group clearly outperformed the self-explanation group for students who applied the strategies with higher quality. Furthermore, higher sketching quality was strongly related to better learning outcomes. Thus, the study's results are more in line with the second account: Sketching can have a beneficial effect on learning above and beyond generating written explanations; at least, if well deployed.